The Impact of Public Education Expenditure on Human Capital, Growth, and Poverty in Tanzania and Zambia : A General Equilibrium Approach - Thorbecke, Erik (IMF Working Papers; Working Paper, 2001)
The impact of public education expenditure on human capital, the supply of different labor skills, and its macroeconomic and distributional consequences is appraised within a multisector CGE model. The model is applied to and calibrated for two Heavily Indebted Poor Countries (HIPCs), Tanzania and Zambia. The simulation results suggest that education expenditure can raise economic growth. However, to maximize benefits from education expenditure, a sufficiently high level of physical investment is needed, as are measures that improve the match between the pattern of educational output and the structure of effective demand for labor. An important result of the simulation experiments is that a well-targeted pattern of education expenditure can be effective for poverty alleviation.